Construção do sentido de feminino na publicidade de marcas de beleza - Lima, Fernanda Ramos de Albuquerque (2020)
In recent years, feminism has again gained relevance, becoming a subject present in the media and in conversations in society. Campaigns led by women on social networks, such as # myfirstharassment, reached thousands of people. Other movements took place in Brazil and in the world, putting feminism and the fight for women's rights in evidence. With this visibility, brands co-opt this discourse and start using it as a selling point in their advertising campaigns. This work has as central problem the identification of the meanings produced in the contemporary advertising speeches of cosmetic brands in the construction of the female beauty simulacrum(s). As hypotheses to be tested, we consider the possibility for consumers to position themselves as determiners of a more inclusive and positive discourse from the articulations allowed by digital networks and, in this scenario, brands use figures of diversity (the black woman, the elderly, the fat and the LGBTQ +) and the discourse of natural beauty to create new simulacrums of women and maintain this dialogue with their consumers. The corpus consists of 17 audiovisual campaigns by the brands Avon and O Boticário, presented on their respective channels on Youtube, from January 2016 to March 2019. To contextualize gender issues in social networks, we use authors such as Manuel Castells, Clay Shirky, Henry Jenkins, Andi Zeisler and Naomi Wolf. For the analysis of the corpus we use the semiotic theory of Algirdas Julien Greimas and his generation of meaning; in Eric Landowski's sociosemiotic strand for the semiotization of simulacrum and treatment of syntax and semantics of the narrative level using the elliptical dynamics of the logic of junction (programming and manipulation regimes) and union (adjustment and accident regimes) from the correlations between interaction, risk and construction of meaning; and in the developments of the plastic semiotics of Ana Claudia de Oliveira to deal with the figurative and plastic configuration of the campaigns and how the homologations between the expression and content plans occur in the enunciative mechanisms of the discursive interactions. As a result, we aim to understand how advertising - as a privileged place for social performances - works in new ways to explore the concepts of beauty and feminine in a time of feminist boiling and questioning of these values. The understanding of the crystallization of values in the analysis of the chosen corpus attests that beauty is the biggest characteristic that advertising wants to maintain and even with the creation of new simulacrums of diverse and empowered women, which demonstrate a small opening to represent beauties different from the white standard European, these representations do not bring significant changes, maintaining the reproduction of stereotypes